2020
DOI: 10.1002/ehf2.12637
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of angiographic findings, procedural success, and timing of percutaneous coronary intervention in cardiogenic shock

Abstract: Aims Urgent revascularization is the mainstay of treatment in acute coronary syndrome (ACS) related cardiogenic shock (CS). The aim was to investigate the association of angiographic results with 90-day mortality. Procedural complications of percutaneous coronary intervention (PCI) were also examined. Methods and results This CardShock (NCT01374867) substudy included 158 patients with ACS aetiology and data on coronary angiography and complications during PCI procedure. Survival analysis was conducted with Kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…CardShock substudy 13 also reported no difference between infarct-related arteries for mortality. In contrast to these two studies, a post hoc analysis 12 reported that patients with left main and proximal left anterior descending artery as a culprit lesion had worse mortality rates compared to those with the others and the right coronary artery was more frequent in the survivor group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…CardShock substudy 13 also reported no difference between infarct-related arteries for mortality. In contrast to these two studies, a post hoc analysis 12 reported that patients with left main and proximal left anterior descending artery as a culprit lesion had worse mortality rates compared to those with the others and the right coronary artery was more frequent in the survivor group.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of TIMI flow and no-reflow for cardiovascular outcome have been well-evaluated. 13,25 The current study used blood carbon dioxide content as a biomarker of tissue hypoxemia instead of arterial lactate because all patients have the information about blood total CO 2 content, which has been used in the shock. 25 In the contemporary era, well-validated, IABP-SHOCK II risk score comprised of six factors: age, stroke, glucose, creatinine, TIMI flow, and arterial lactate.…”
Section: Discussionmentioning
confidence: 99%
“…Также существенным общим недостатком большинства предложенных шкал является тот факт, что они не учитывают результаты проведенного ЧКВ [6][7][8][9][10][11][12][13]. При этом непосредственный успех вмешательства является важнейшим залогом благоприятного прогноза в лечении пациентов с острым ИМпST [14,15].…”
Section: Introductionunclassified